Optimalisasi Manajemen Masjid dalam Meningkatkan Kualitas Pelayanan Jemaah Masjid Al-Jabbar - Falah, Mukhlis Miftahul; Fitriani, Putri Diesy (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to determine how the management of the Al-Jabbar mosque in an effort to improve the quality of service seen from planning, formation of organizational structure, implementation of planning, to the supervision process. The theory used in this study refers to the theory of management functions put forward by Henry Fayol and G.R. Terry, which explains the Management Function consisting of the planning, organizing, implementing and supervising processes. In addition, using the theory of service quality put forward by Parasuraman et al., there are several indicators that determine the quality of service, namely reliability, responsiveness, assurance, empathy, tangible (direct evidence). This study uses a descriptive research method through a qualitative approach. Data collection in this study was carried out using observation, interview, and documentation techniques. The results of this study show the commitment of the Al-Jabbar Mosque to continue to improve in optimizing services to the congregation with various programs that are run both directly and indirectly. Improvements start from planning to compile programs or forms of service plans provided, organizing to form human resources that are able to meet the needs of the congregation, the implementation process that always provides improved services to the congregation, to supervision that tries to be sensitive to situations both internal (Al-Jabbar Mosque) and external (congregation needs), because every need and complaint of the congregation becomes material for evaluation to improve the quality of congregation services at the Al-Jabbar Mosque.